Land Cover Change Analysis: A Case Study of Suryabinayak Municipality - Kumar Basnet, Ram; Nhemaphuki, David; Ghimire, Subash; Upadhyaya, Pradeep Sapkota; Khatri, Dinesh (Journal on Geoinformatics, Nepal, 2026)
This research examines how the Land cover (LC) have consistently changed in past eight years of timeframe from 2016 to 2024 in Suryabinayak Municipality with the help of remote sensing and GIS techniques. This study employed Sentinel-2 imagery, which underwent pre-processing, followed by the application of the random forest algorithm to classify land cover for the years 2016, 2020, and 2024 using Google Earth Engine. After classifying the images, accuracy assessments were conducted to evaluate the reliability of these classifications. Subsequently, spatial pattern analyses were performed on the classified images to examine land cover changes over time. Additionally, a literature review was conducted to identify the causes and impacts of urbanization within the study area, drawing from various research studies. The results show from 2016 to 2024, vegetation suffered the most loss, with built-up areas experiencing increase along the roads and minimal change in agricultural land. This analysis showed a conversion trend where vegetation was primarily transformed into agricultural land, which was then developed into urban areas. At the ward level, wards 2 & 3 (Balkot) and wards 5 & 6 (Katunje) exhibited pronounced urbanization, with built-up areas exceeding those of other wards. The rising number of parcels in Chitpol and Sipadol underscores the increasing demand for land, reflecting ongoing urban growth. Internal migration was identified as a key driver of urbanization, with individuals relocating to urbanfareas for better opportunities. This research underscores the significant changes in LC within the Suryabinayak Municipality, largely driven by urbanization. This rapid urban growth not only threatens environmental sustainability but also triggers demographic changes, resulting in a decline in rural populations.